2021
DOI: 10.1186/s12931-021-01719-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between long non-coding RNA PCAT-1 expression and gefitinib resistance in non-small-cell lung cancer cells

Abstract: Background Gefitinib, an epidermal growth factor receptor tyrosine kinase inhibitor, has been used as first-line treatment for advanced non-small-cell lung cancer (NSCLC). However, during treatment, cancer cells often develop resistance to gefitinib, the mechanisms of which are not fully understood. This study was designed to elucidate the expression and role of long non-coding RNA (lncRNA)-PCAT-1, a potential biomarker for drug resistance and a therapeutic target for NSCLC, in gefitinib resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Thereby, lncRNA H19 seems to be a key factor in regulating RTK signaling [ 178 ]. RTKIs with a similar effect on the mentioned pathways on UCA1 [ 179 ], CRNDE [ 180 ], and PCAT1 [ 181 ] genes lead to the development of other types of NSCLCs. In an alternative mechanism, LncRNA-SARCC functions as a suppressor of the androgen receptor (AR) protein, hindering the propagation of its downstream signals involving AKT, MMP-13, K-RAS, and P-ERK.…”
Section: Long Non-coding Rtk-rnasmentioning
confidence: 99%
“…Thereby, lncRNA H19 seems to be a key factor in regulating RTK signaling [ 178 ]. RTKIs with a similar effect on the mentioned pathways on UCA1 [ 179 ], CRNDE [ 180 ], and PCAT1 [ 181 ] genes lead to the development of other types of NSCLCs. In an alternative mechanism, LncRNA-SARCC functions as a suppressor of the androgen receptor (AR) protein, hindering the propagation of its downstream signals involving AKT, MMP-13, K-RAS, and P-ERK.…”
Section: Long Non-coding Rtk-rnasmentioning
confidence: 99%
“…Wang et al also reported that knockdown of long non-coding RNA (lncRNA)-PCAT-1, an important factor in resistance to ge tinib in NSCLC cells, could improved the sensitivity to ge tinib, increase apoptosis, and inhibit GSK3 and AKT phosphorylation in H1299/GR cells. Thus this lncRNA could be a potential target for enhancing ge tinib e cacy (110). In another study by Satoh et al, combination therapy with erlotinib, bevacizumab plus osimertinib after acquired resistance emerged in NSCLC patients could be an option for these patients suffering from acquired resistance therapy to osimertinib alone (111).…”
Section: Intrinsic and Acquired Resistance To Rtkis In Different Cancersmentioning
confidence: 99%
“…Sun et al reported that lncRNA hyaluronan synthase 2 antisense 1 (HAS2-AS1) promoted the NSCLC tumorigenesis and gefitinib resistance of NSCLC by repressing the EphB3 via recruiting LSD1 [ 123 ]. Wang et al showed that PCAT-1 was highly expressed in gefitinib-resistant NSCLC tissues and cells, and PCAT-1 knockdown sensitized NSCLC to gefitinib by inhibiting AKT and GSK3 phosphorylation in NSCLC [ 124 ]. PCAT6 has been found to confer to gefitinib resistance of NSCLC via miR-326/IFNAR2 axis [ 125 ].…”
Section: Lncrnas and Nsclc Egfr-tkis Resistancementioning
confidence: 99%